1988
DOI: 10.1038/jcbfm.1988.136
|View full text |Cite
|
Sign up to set email alerts
|

Reoxygenation and Calcium-Induced Cerebroarterial Contractions as Affected by Vasodilator Agents

Abstract: Summary: In helical strips of dog cerebra� arterie . s . ex posed to Ca2+ -free medium under hYPoxlc condltions (95% N 2 and 5% CO 2 ), prostaglandin (PO) F 2 1l produced a slight tonic contraction. The addition . of Ca2+ evok � d a phasic contraction followed by relax�t � on and a sus . t � med contraction, and reoxygenation ehclt � d an addltIOnal The mechanical responses of isolated cerebral ar teries to vasodilator substances differ from those of extracerebral arteries. For instance, Ca 2 + entry blockers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…When aorta rings were exposed to Ca 2+ -free media, addition of phenylephrine 10 −6 M elicited a small tonic contraction induced mainly by intracellular Ca 2+ release from endoplasmic reticulum stores 15. Pretreatment of endothelium-denuded rings with cinnamaldehyde 5.0 × 10 −5 g/mL significantly reduced phenylephrine-induced contraction under extracellular Ca 2+ -free conditions (Figure 6C).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…When aorta rings were exposed to Ca 2+ -free media, addition of phenylephrine 10 −6 M elicited a small tonic contraction induced mainly by intracellular Ca 2+ release from endoplasmic reticulum stores 15. Pretreatment of endothelium-denuded rings with cinnamaldehyde 5.0 × 10 −5 g/mL significantly reduced phenylephrine-induced contraction under extracellular Ca 2+ -free conditions (Figure 6C).…”
Section: Resultsmentioning
confidence: 91%
“…Vascular endothelium plays a key role in maintaining normal function of the vasculature 15. Endothelial cells release endothelium-dependent vasodilators, such as nitric oxide and prostacyclin (prostaglandin I 2 ), upon stimulation of various factors in the blood stream and as a result of physiological stress 15,16.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is reported that beraprost increases pre-and postischemic pial arterial diameter of cats (Tanaka et al, 1988), and dilates the isolated cerebral artery from the dog (Akiba et al, 1986) and human (Kobayashi et al, 1989) at concentrations more than 10 -8M. Furthermore, diltiazem, a vasodilator with very weak antiplatelet activity (Lippton et al, 1984;Bian and Toda, 1988), improved survival and convulsion rates in AA-induced sudden death in rabbits. From these facts, although the antithrombotic effect may play a major role, the involvement of vasodilation cannot be denied completely.…”
Section: Discussionmentioning
confidence: 99%